Do Tunisian Universities need organizational commitment? - HAJRI, Mehdi (Advances in Social Sciences Research Journal, 2021)
Higher Education is a real lever of growth for developing countries such as Tunisia. The aim of our study is to show the importance of organizational commitment in the intention of running the university well. As a result, the review of the literature enabled us to analyze a concept of attitude at work, namely organizational commitment, which in our opinion can constitute a major lever for carrying out the university development strategies. It has been established that academics remain committed to their vocation and thereby demonstrate their continued commitment to their students despite the workload, administrative tasks and research carried out (Houston et al., 2006).